KEBIJAKAN HUKUM PIDANA DALAM PENANGGULANGAN KORUPSI BIROKRASI PADA SEKTOR PELAYANAN PUBLIK - Warfian Saputra (Wajah Hukum, 2018)
Analyzes of criminal policy and criminal law that criminal purpose is not just a retaliation to persons who have committed criminal acts but furthermore aims to create more useful community interests. In addition, criminal justice is impossible to devote all his energy and his thoughts on an important matter if at the same time having tomeladeni and completing the number of things that are small and insignificant. In accordance with the above statement, then the problems in this paper is how Policy Formulation of criminal law about bureaucratic corruption in the public service at this time and the time will come.Keyword: inform policy, corruption, bureaucracy, public service